The Ability of Brand Trust as a Mediator on the Determinants of Customer Loyalty: Study on Mie Sagu Waraka (SAWA) in Ambon, Indonesia - Tabelessy, Walter (HM Publisher, 2024)
The aim of this research is to investigate the determinants of customer loyalty for Mie Sagu Waraka (SAWA) in Ambon, which is analyzed using the factors of brand image, brand trust, product differentiation, and purchasing decisions, as well as testing the ability of brand trust as a mediating variable. This research is explanatory research using a questionnaire to obtain data from respondents, as many as 171 Mie Sagu Waraka (SAWA) customers obtained using a purposive sampling technique. PLS-SEM as a data analysis technique was used to test the hypothesis proposed in this research and analyzed using the help of the SmartPLS version-4 application. The results of data processing found that brand image does not have a significant influence on customer loyalty, brand trust has a significant influence on customer loyalty, image brand has a significant influence on brand trust, product differentiation has a significant influence on customer loyalty, purchasing decisions have a significant influence on customer loyalty, and product differentiation has a significant influence on purchasing decisions, and brand trust is able to significantly mediate the relationship between brand image and customer loyalty.